An anatomical basis for the neck-tongue syndrome. Issue 3 (March 1981) - Bogduk, N
Abstract : The C2 nerve roots and rami were dissected in five cadavers to explore the pathogenesis of Neck-Tongue Syndrome. The most likely cause of the simultaneous occurrence of suboccipital pain and ipsilateral numbness of the tongue is an abnormal subluxation of one lateral atlanto-axial joint with impaction of the C2 ventral ramus against the subluxated articular processes.